Lost moon : the perilous voyage of Apollo 13 - Lovell, Jim.; Kluger, Jeffrey (Boston : Houghton Mifflin, 1994)
Astronaut Lovell chronicles his harrowing, nearly fatal, failed mission to the moon, describing his crew's ingenuity in returning safely to Earth. The untold story of the American moon shot that almost ended in a fatal catastrophe, told by the flight's commander, offers a thrilling chronicle of courage, heroism, and adventure.
Includes index.
Keywords: Apollo 13 (Spacecraft) -- Accidents; Space vehicle accidents -- United States; Lovell, Jim